Pemahaman Beban Ganda Perempuan di Tengah Pandemi: Pengalaman Dari Mantan TKW Anggota Muslimat NU di Kecamatan Kras - Laily Purnawati (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Women who work as female workers from the start have already borne a double burden in their families. Apart from being given the task of carrying out domestic duties even though they are physically not at home, on the other hand they have to work to help meet their household needs. This condition continues even though these former TKWs have returned home. There are many ways that these former TKWs can continue to help make a living, especially during a pandemic where many husbands have lost their source of income. The method used is a type of qualitative research by taking data through in-depth interviews and observations. The resource persons were former women TKW who were also members of the Muslimat NU. The interviews were conducted to find out whether they understood the double burden that she had to do and how these former women TKW received their double burden. The conclusions obtained from this study were former women. These migrant workers in the midst of a pandemic are experiencing extraordinary problems. Most of them choose only as side workers, namely "oncek" melinjo on the grounds that they can be done from home while still supervising their children. This is where NU Muslims as one of the social organizations in Indonesia also attend and provide provisions for these women to understand the double burden they receive. , especially their provision in the field of faith so that they are physically and mentally ready to carry out this mandate.